Examining the case for class analysis in adult education research - Michael Collins; Sue Collard (Adult Education Research Conference, 1995)
An explanation is given for the absence of class analysis in North American adult education discourse. Various perspectives on class analysis are examined. A case is made for class analysis and class action in adult education research and practice.